Estimation of nitrous oxide emissions from rice paddy fields using the DNDC model: a case study of South Korea. (27th August 2022) - Khokhar, Nadar Hussain; Ali, Imran; Maitlo, Hubdar Ali; Abbasi, Naeem; Panhwar, Sallahuddin; Keerio, Hareef Ahmed; Ali, Asim; Uddin, Salah
Abstract: The Denitrification-Decomposition (DNDC)-Rice is a mechanistic model which is widely used for the simulation and estimation of greenhouse gas emissions [nitrous oxide (N2 O)] from soils under rice cultivation. N2 O emissions from paddy fields in South Korea are of high importance for their cumulative effect on climate. The objective of this study was to estimate the N2 O emissions and biogeochemical factors involved in N2 O emissions such as ammonium (NH4 + ) and nitrate (NO3 − ) using the DNDC model in the rice-growing regions of South Korea. N2 O emission was observed at every application of fertilizer and during end-season drainage at different rice-growing regions in South Korea. Maximum NH4 + and NO3 − were observed at 0–10 cm depth of soil. NH4 + increased at each fertilizer application and no change in NO3 − was observed during flooding. NH4 + decreased and NO3 − increased simultaneously at end-season drainage. Minimum and maximum cumulative N2 O emissions were observed at Chungcheongbuk-do and Jeju-do regions of South Korea, respectively. The simulated average cumulative N2 O emission in rice paddies of South Korea was 1.37 kg N2 O-N ha −1 season −1 . This study will help in calculating the total nitrogen emissions from agriculture land of South Korea and the World. HIGHLIGHTS: We successfully simulated N2 O emission from rice paddy fields of South Korea. DNDC model was used to estimate N2 O emission in South Korea. Biogeochemical factors of soil such as NH4 + and NO3 − concentration were also focused upon. Simulated N2 O emission in this study was strongly correlated as R 2 = 0.88–0.90. Results may help to estimate the nitrogen budget of South Korea as well as the world. Graphical Abstract